Factors related to mothers' compliance with MR immunization - Prihatiningsih, Prihatiningsih; Utami, Rahayu Budi; Damayanti, Dini Fitri (Borneo Scientific Publishing, 2024)
The Measles–Rubella (MR) vaccine is a combined vaccine intended to prevent measles and rubella, two infectious diseases that can cause serious health complications in children and women of reproductive age. Despite the national MR immunization program, coverage remains suboptimal in several areas. Data from the Tuan Tuan Community Health Center, Benua Kayong District, in 2018 showed that during School Children Immunization Month (BIAS), only 281 out of 767 elementary school students received the MR vaccine, and five elementary schools refused MR immunization due to parental considerations. This study aimed to analyze factors associated with maternal compliance with MR immunization among elementary school students in the working area of the Tuan Tuan Community Health Center, Ketapang Regency. This study employed an analytical cross-sectional design. The sample consisted of 106 parents of first-grade elementary school students in Tuan Tuan Village, Benua Kayong District, Ketapang Regency. Samples were selected using simple random sampling, with proportional sampling applied to each elementary school. Data were collected using a structured questionnaire and analyzed statistically. The results showed that maternal age was significantly associated with MR immunization compliance, while maternal occupation, socioeconomic status, and maternal knowledge were not associated with compliance. Environmental support was found to have a significant relationship with maternal compliance with MR immunization. In conclusion, maternal age and environmental support were factors associated with maternal compliance with MR immunization among elementary school students in Tuan Tuan Village. Strengthening environmental support and targeted health education may improve MR immunization coverage in this area.